Effects of different levels of protein supplementary diet on gene expressions related to intramuscular deposition in early‐weaned yaks. (23rd January 2014) - Zhang, Hai‐bo; Wang, Zhi Sheng; Peng, Quan‐Hui; Tan, Cui; Zou, Hua‐Wei
Abstract This study was conducted to estimate different levels of protein supplementary diet on gene expressions related to intramuscular deposition in early‐weaned yaks. Results showed that supplementary dietary protein significantly increased final weight, average daily gain (ADG), intramuscular fat (IMF), serum free fatty acid (FFA), total triglycerides, total cholesterol (Ch), low‐density lipoprotein cholesterol (LDL) and high‐density lipoprotein cholesterol (HDL) content. There was a quadratic response of ADG, IMF, FFA, Ch, HDL and LDL to dietary crude protein (CP) level. Lipoprotein lipase (LPL), fatty acid synthase (FAS) and acetyl‐CoA carboxylase (ACC) enzyme activities were significantly increased by supplementary dietary CP, while hormone‐sensitive lipase (HSL) and carnitine palmitoyltransferase‐1 (CPT‐1) activities were significantly decreased. LPL, ACC and FAS enzyme activities showed quadratic increase as dietary CP increased. Peroxisome proliferator‐activated receptor γ (PPARγ), LPL, FAS, sterol regulatory element binding protein 1 (SREBP‐1), ACC, stearoyl‐CoA desaturase (SCD) and heart fatty‐acid binding protein (H‐FABP) gene expression were significantly increased by supplementary dietary CP, while HSL and CPT‐1 gene expression were significantly decreased. PPARγ, LPL, SREBP‐1, ACC and H‐FABP gene expression showed quadratic increase as dietary CP increased. These results indicated that supplementary dietary protein increased IMF accumulation mainly to increased intramuscular lipogenic gene expression and decreased lipolytic gene expression.